Long-term medical and social consequences of underage labor - E. S. Mikhaylin (Акушерство, гинекология и репродукция)
The long-term effects (marital status, attitude to breastfeeding, re-pregnancy rate) underage (aged 13-17 years) labor who gave birth within and outside the specialized educational program were studied. It was revealed that the girls who attended program classes, continued breastfeeding significantly longer. At the same time, no significant difference in the frequency of early re-pregnancy was found. Apparently, educational programs are not effective enough and require revision.